2018
DOI: 10.3390/ma11060883
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Resistance and Wetting Behavior of MgO-C Refractories: Effect of Carbon Content

Abstract: Various carbon contents in the MgO-C refractory were studied with respect to the oxidation resistance and the wetting behavior with slag. The bulk density, apparent porosity, cold crushing strength, oxidation rate, and mass loss rate of the fired MgO-C refractories with various carbon contents were measured and compared. The wetting and penetration behavior of the cured MgO-C refractory with the molten slag were observed in-situ. The contact angle and the shape parameters of molten slag, including the apparent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 26 publications
(30 reference statements)
1
22
0
Order By: Relevance
“…Carbon in the MgO–C refractory can depress the wettability between the refractory and the slag. [ 24,25 ] Therefore, the large consumption of carbon in refractory could lead to the slag penetrated the refractory more easily. Moreover, several studies indicated that the viscosity of molten is of vital importance to the penetration behavior and changed during the smelting process, which is significant to help to understand the internal relationship among the chemical composition, physical property, and corrosion ability of the molten slag.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon in the MgO–C refractory can depress the wettability between the refractory and the slag. [ 24,25 ] Therefore, the large consumption of carbon in refractory could lead to the slag penetrated the refractory more easily. Moreover, several studies indicated that the viscosity of molten is of vital importance to the penetration behavior and changed during the smelting process, which is significant to help to understand the internal relationship among the chemical composition, physical property, and corrosion ability of the molten slag.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the thickness of the slag layer on the surface of the MgO particle in refractory sample without pre‐treatment was thin (see Figure 5b) due to the anti‐wetting effect of graphite on molten slag. [ 24,25 ] A microscopic analysis showed that the corrosion depth of the refractory untreated specimen in contact with M1 slag was about 0.28 mm, whereas the corrosion depth for the pre‐treatment specimen was about 1.70 mm.…”
Section: Resultsmentioning
confidence: 99%
“…The porosity and pore size distribution were analyzed by using mercury porosimetry (AutoPore IV 9500, Micromeritics, Shanghai, China). The bulk density was measured by the Archimedes method in water medium, as shown in Equation (1) [14]. Three independently measured density values are average out and reported as the density of the sintered sample:Db=m1DLm3m2 where D b refers to the bulk density, D L represents the density of water, m 1 corresponds to the mass of the sample dried in air, m 2 denotes the mass of the sample in water and m 3 refers to the mass of the sample with free bubbles on the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Carbon-containing refractories, which exhibit excellent thermal shock resistances and corrosion resistances because of the additional carbon, have been widely applied over the last few decades [1,2]. However, the high carbon contents (10–20 wt.%) in current commercialized carbon-containing refractories leads to serious complications, such as inferior oxidation resistance, high thermal conductivity, high carbon pick-up in molten steel, and corresponding degradation of the mechanical properties of the products [3,4,5].…”
Section: Introductionmentioning
confidence: 99%